Enhancing stability of echium seed oil and beta-sitosterol by their coencapsulation by complex coacervation using different combinations of wall materials and crosslinkers. (30th June 2018) - Comunian, Talita A.; Nogueira, Marina; Scolaro, Bianca; Thomazini, Marcelo; Ferro-Furtado, Roselayne; de Castro, Inar Alves; Favaro-Trindade, Carmen S.
Highlights: Sinapic acid (SA) represents a suitable alternative to traditional crosslinkers. Echium oil and phytosterols were protected when encapsulated by complex coacervation. 0.075 g SA/ g gelatin was the best concentration for protection of compounds. Abstract: Intake of omega-3 fatty acids and phytosterols aids in the reduction of cholesterol and serum triglycerides. However, both fatty acids and phytosterols are susceptible to oxidation. This work coencapsulated echium oil (source of stearidonic and alpha-linolenic fatty acids) and beta-sitosterol (phytosterol) by complex coacervation using different combinations of wall materials, and sinapic acid (SA) and transglutaminase as crosslinkers. High encapsulation yields were obtained (29–93% for SA; 68–100% for the mixture of oil and phytosterols) and retention of 49–99% and 16% for encapsulated and free SA, at 30 days-storage. Treatment with gelatin-arabic gum and 0.075 g SA/g gelatin showed the best results: 0.07 mg MDA/g capsule, and retention of 96, 90 and 74% for alpha-linolenic, stearidonic acid and beta-sitosterol at 30 days of storage, respectively. Thus, coencapsulation of echium oil and phytosterol using SA as the crosslinker was possible, obtaining effective vehicles for protection and application of these compounds in foods.